Determining dengue virus serostatus by indirect IgG ELISA compared with focus reduction neutralisation test in children in Cebu, Philippines: a prospective population-based study. Issue 1 (January 2021) - Lopez, Anna Lena; Adams, Cameron; Ylade, Michelle; Jadi, Ramesh; Daag, Jedas Veronica; Molloy, Caitlyn T; Agrupis, Kristal An; Kim, Deok Ryun; Silva, Maria Wilda; Yoon, In-Kyu; White, Laura; Deen, Jacqueline; et al.
Summary: Background: Detection of dengue virus antibodies is important for understanding future dengue virus risk and for prevaccination screening. We aimed to evaluate the performance of a dengue IgG indirect ELISA in determining dengue seroprevalence in a cohort of children in the Philippines, using a focus reduction neutralisation test (FRNT) as the reference test. Methods: In this prospective population-based cohort study, we enrolled healthy children residing in Bogo or Balamban, Cebu, Philippines, who were to be aged 9–14 years at the time of a mass dengue vaccination campaign. Sera were collected from participants and batch tested by indirect IgG ELISA and FRNT. The primary endpoint was dengue seroprevalence in the cohort, detected by ELISA, and validated by that detected by reference FRNT. This study is registered with ClinicalTrials.gov, NCT03465254 . Findings: We collected 2996 serum samples between May 2, and June 2, 2017, and we tested each sample with IgG ELISA. Using 1961 samples (65·5%) that were tested with FRNT, and 1035 samples (34·5%) with imputed results, we found that 320 (10·7%) of 2996 children were dengue naive and 2676 (89·3%) were seropositive for previous dengue virus infection. Based on the 1961 non-imputed FRNT results classified as dengue seronegative or seropositive, the ELISA (with a 0·9 index value cutoff) showed 95·2% sensitivity, 93·4% specificity, 6·6% false positivity, and 4·8% false negativity. However, sensitivity of the ELISA was poor (77·1%) among children with immunity to just one dengue virus serotype. Of the 11 sera that were false positive with ELISA, seven samples (63·6%) were seropositive for Zika virus or Japanese encephalitis virus with FRNT. Interpretation: Most children (89·3%) assessed in our study and eligible to participate in the mass dengue vaccination campaign were seropositive for previous dengue virus infection. Compared with FRNT, ELISA had high sensitivity and specificity (>90%), but the false-negative and false-positive rates makes the test suboptimal for prevaccination screening. Individuals who are falsely identified as seropositive by dengue IgG ELISA and then vaccinated might be at risk of developing severe disease during a subsequent exposure to wild-type dengue virus. Those with a monotypic profile would benefit the most from vaccination, but the sensitivity of the IgG ELISA was much lower in this group than in those with a multitypic profile. Funding: Philippine Department of Health, Hanako Foundation, WHO, Swedish International Development Cooperation Agency through the International Vaccine Institute, and University of North Carolina, Chapel Hill, NC, USA.